Vera Frenkel : The Institute (tm) : Or, What We Do for Love = L'Institut (md) : Ou, que ne ferait-on pas par amour. - Adams, Annmarie; Frenkel, Vera; Jones, Mark J.; Legge, Elizabeth; Rokeby, David; Schwartz, Judi; Tuer, Dot; Exhibition. Vera Frenkel : The Institute (tm) = L'Institute (md) (1). Exhibition. Vera Frenkel : The Institute (tm) = L'Institute (md) (2). Exhibition. Vera Frenkel : The Institute (tm) = L'Institute (md) (3). Art Gallery of Sudbury. Carleton University Art Gallery Ottawa. Justina M. Barnicke Gallery, Hart House, University of Toronto Toronto. 2003-11-18. 2004-09-09. 2004-11-15. 2003-12-18. 2004-10-17. 2005-01-23 (Toronto : Hart House, University of Toronto, 2003)
Frenkel's remarkable work on the inner life of a dysfunctional cultural institution has reached the mid-point of its run at the Justina M. Barnicke Gallery. Viewers are invited into the first test branch of The National Institute for the Arts (known informally as The institute (tm), a chain of artists' residences situated in vacant hospitals across the country. The on-line element of the work, accessible at www.the-national-institute.org is part of the full multidisciplinary project still on view in the gallery. Moving freely between the real and the fictive, visitors will meet the artists in residence who live and work under the auspices of a government scheme to retrain unemployed cultural bureaucrats as caregivers. In combining a quasi-fictional structure and compelling documentary content, Frenkel has devised an instrument that engages both conscience and desire. The exhibition featuring The Institute (tm) web site accompanied by related audio works, plaques and digital prints, traces a ship-of-fools situation where viewers can be both amused and saddened by the curious relation between the arts, the health system and government.
biog. p. 90-91 (eng.), p. 92-93 (frans)
Engels
Frans
boek
Keywords: Frenkel, Vera